Communication : effective communication techniques to improve your public speaking and social skills - Scott, Ste (Middletown, DE : CreateSpace Independent Publishing Platform, 2016)
Techniques to Improve Your Public Speaking and Social Skills". No matter who you are, and whatever it is that you are doing in life, being able to communicate is definitely one of the things that you should learn. After all, you wouldn't be able to tell people what you want or what they need to know if you don't know how to speak up-even just a bit.
Chapter 1: Start from the Outside - Fake It 'til You Make It! -- Chapter 2: Try Getting Rid of Fillers -- Chapter 3: Practice with the Mirror-Have Some Charisma! -- Chapter 4: Learn How to Work with a Crowd -- Chapter 5: Talk Like You're a Friend-Not a Superior -- Chapter 6: Learn to Coerce Nicely--Use Your Charm! -- Chapter 7: Be More of Yourself -- Chapter 8 : Perfection Is Just a Thought - Opt for Realism, Instead -- Chapter 9: Learn to Be Spontaneous -- Chapter 10: Know What You Are Talking About -- Chapter 11: Have Proper Social Skills -- Chapter 12: End Your Speaking Fears with Some Questions.
Keywords: COMMUNICATION